Optimization of multiplex PCR conditions for rapid detection of Escherichia coli O157:H7 virulence genes - Ranjit Singh, Jeshveen Singh; Chai, Lay Ching; Pui, Chai Fung; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The main source of E. coli 0157:H7 is cattle, but recent studies showed high percentage of outbreaks contributed by contaminated water. The occurrence of E. coli O157:H7 in environmental water samples poses a potential threat to human health. The aim of this study was to establish a protocol for the detection of the pathogen E. coli O157:H7 and E. coli virulence genes (eaeA, rfbE, hly, stx 1, and stx 2) in a multiplex PCR protocol using six specific primer pairs. The target genes produced species-specific amplicons at 625 bp, 397 bp, 296 bp, 166 bp, 210 bp and 484 bp for E. coli O157:H7 (fliC h7 gene) and virulence genes (eaeA, rfbE, hly, stx 1, and stx 2) respectively. The results obtained show that the established PCR protocol is suitable for a rapid and specific analysis of the pathogenic E. coli O157:H7 in environmental water samples for the assessment of microbiological risks.